LEGAL PROTECTION OF CONSUMER RIGHTS IN THE CONCEPT OF HUMAN RIGHTS - Sudanto; Asrizal Saiin; Zaitun (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2022)
Economic development includes various interrelated development sectors. One form of this linkage is related to the protection of consumer rights which is closely related to human rights issues. Thus the importance of the issue of legal protection for consumer rights, this research tries to specifically highlight the concept of human rights, where the main focus is on the role of Law No.8 of 1999 in protecting consumer rights as human rights, as well as consumer advocacy efforts. This research is to answer whether consumers really are sufficiently protected by laws based on human rights. This research is legal research normative, namely research on secondary data obtained through library studies. From this research, it is found that consumer protection laws do not appear to provide protection for consumers in general anymore, but actually provide full protection for consumers in various forms of transactions, both transactions in the form of products and transactions in the form of services that can potentially harm the consumer of their rights.